Peningkatan Produksi Ikan Pada Sistem Sawah Tambak Di Desa Rayunggumuk Glagah Lamongan - ating yuniarti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2018)
This community service was carried out to support the fish farmers in solving their problems. The problems identified during the initial survey were: high feed cost, low survival rate of cultured fish and shrimp, disease outbreaks and lack of production and financial management. Workshop, training and applying a simple technology was introduced to the selected farmers. Some activities conducted were: (1) providing two hand refractometers and a pelleting machine, (2) workshop of local-ingredient based fish feed production, (3) workshop of probiotics production, (4) training of production and financial management, (5) demo-pond. Farmers have been able to produce local-ingredient based fish feed and probiotics as well as to apply a simple production and financial management. The demo pond results showed that introducing of hand refractometer for adaptation period could increase the survival rate of fish and shrimp up to 25%. Furthermore, by applying local-ingredient based fish feed and probiotics during the culture periods, the fish famers could increase the income from fish production up to 50.1%.